Encoding of Passive Anticollision Radio Frequency Identification Surface Acoustic Waves Tags - Alexander Sorokin; Alexander Shepeta; Maurits Wattimena (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper describes the encoding of anticollision radio-frequency identification tags based on surface acoustic waves. The study is based on the tag model with specific topology, which allows us to receive a response signal with time–frequency information. This research considers the collision case for several passive tags. Therefore, the proposal is to analyze the possibility of using several distinctive signs like frequency and time. We consider the model of passive surface acoustic wave tag, which contains piezoelectric substrate, interdigital transducer, and consecutive orthogonal-frequency-coded structures, which are placed in time slots. Similar topology makes possible the reliability of increasing tag identification in the collision case.